2016
DOI: 10.1073/pnas.1515641113
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of nitrogen fixation in eastern tropical South Pacific surface waters

Abstract: An extensive region of the Eastern Tropical South Pacific (ETSP) Ocean has surface waters that are nitrate-poor yet phosphate-rich. It has been proposed that this distribution of surface nutrients provides a geochemical niche favorable for N 2 fixation, the primary source of nitrogen to the ocean. Here, we present results from two cruises to the ETSP where rates of N 2 fixation and its contribution to export production were determined with a suite of geochemical and biological measurements. N 2 fixation was on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
105
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 56 publications
17
105
1
1
Order By: Relevance
“…The BNF activity detected in this study is a further evidence that high nitrate concentrations (and high N:P ratios) do not inhibit BNF activity, such as it was also observed in other upwelling regions (e.g., Voss et al, 2004;Sohm et al, 2011;Subramaniam et al, 2013;Benavides et al, 2014). Indeed, recent studies demonstrated that BNF can occur upon exposure to elevated DIN (nitrate and/or ammonium), as long as phosphate is available (Knapp, 2012), and point toward iron as the primary control factor of BNF (Knapp et al, 2016;Bonnet et al, 2017). Thus, the sensitivity of marine BNF to high DIN is not clear.…”
Section: Magnitude and Biogeochemical Relevance Of Bnfsupporting
confidence: 77%
“…The BNF activity detected in this study is a further evidence that high nitrate concentrations (and high N:P ratios) do not inhibit BNF activity, such as it was also observed in other upwelling regions (e.g., Voss et al, 2004;Sohm et al, 2011;Subramaniam et al, 2013;Benavides et al, 2014). Indeed, recent studies demonstrated that BNF can occur upon exposure to elevated DIN (nitrate and/or ammonium), as long as phosphate is available (Knapp, 2012), and point toward iron as the primary control factor of BNF (Knapp et al, 2016;Bonnet et al, 2017). Thus, the sensitivity of marine BNF to high DIN is not clear.…”
Section: Magnitude and Biogeochemical Relevance Of Bnfsupporting
confidence: 77%
“…Rates of N 2 fixation can either be expressed indirectly as ethylene (C 2 H 4 ) produced from acetylene (C 2 H 2 ) using the acetylene reduction assay (ARA), or directly as the amount of nitrogen assimilated using 15 N 2 tracer experiments (see Box 1). The lowest rates have been recorded in the water column (Capone, 2001;Foster et al, 2009;Knapp et al, 2016), compared to benthic environments such as reef sediments and hard substrates which often present high N 2 fixation activities (Davey et al, 2008;O'Neil and Capone, 2008;Bednarz et al, 2015b;Rix et al, 2015). Epilithic communities recovering coral rubbles or dead coral skeletons can indeed fix up to 12 and 27 nmol N cm −2 h −1 , respectively (Davey et al, 2008).…”
Section: N 2 Fixation In Coral Reef Ecosystems Description Of N 2 Fixmentioning
confidence: 99%
“…More recently, the Eastern Tropical South Pacific (ETSP) has seen increased sampling due to nutrient distribution-based modelling predictions that the highest global N 2 fixation rates would be found in surface waters above 25 and adjacent to oxygen deficient zones (ODZs), where significant phosphorus (P) would be available to support N 2 fixation (Deutsch et al, 2007). However, field campaigns have found exceedingly low rates of N 2 fixation in the ETSP gyre (Knapp et al, 2016a;Raimbault and Garcia, 2008 2008), which have been attributed to limited iron availability (Dekaezemacker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Multiplying the fraction of export production supported by N 2 fixation (x) by the PN sink mass flux provides a time-integrated N 2 fixation rate that can be compared with 15 N 2 incubation-based N 2 fixation rate measurements (Knapp et al, 2016a). Here it is hypothesized that both rates of N 2 fixation and its 10 importance for fuelling export production will be higher at stations in the western vs. central and eastern regions of the WTSP because of their closer proximity to iron sources (Guieu et al, under review).…”
mentioning
confidence: 99%